Synergistic Cr(VI) Reduction and Chloramphenicol Degradation by the Visible-Light-Induced Photocatalysis of CuInS2: Performance and Reaction Mechanism - Zhu, Chaosheng; Li, Jingyu; Chai, Yukun; Zhang, Yongcai; Li, Yunlin; Zhang, Xiangli; Liu, Jin; Li, Yan (Frontiers in Chemistry, 2022)
Despite significant scientific efforts in the field of water treatment, pollution of drinking water by toxic metal ions and synthetic organic compounds is becoming an increasing problem. The photocatalytic capabilities of CuInS2 nanoparticles were examined in this study for both the degradation of chloramphenicol (CAP) and the reduction of Cr(VI). CuInS2 nanoparticles were produced using a straightforward solvothermal approach and subsequently characterized by many analysis techniques. Simultaneous photocatalytic Cr(VI) reduction and CAP oxidation by the CuInS2 nanoparticles under visible-light demonstrated that lower pH and sufficient dissolved oxygen favored both Cr(VI) reduction and CAP oxidation. On the basis of active species quenching experiments, a possible photocatalytic mechanism for Cr(VI) conversion with synchronous CAP degradation was proposed. Additionally, the CuInS2 retains a high rate of mixed pollutant removal after five runs. This work shows that organic contaminants and heavy metal ions can be treated concurrently by the visible-light-induced photocatalysis of CuInS2.